Stigma and discrimination tendencies towards COVID-19 survivors: Evidence from a nationwide population-based survey in Ghana - Eric Osei; Hubert Amu; Prince Kubi Appiah; Solomon Boamah Amponsah; Evans Danso; Samuel Oppong; Comfort Worna Lotse; Bright Emmanuel Owusu; Simon Azure Agongo; Eliasu Yakubu; Gideon Kye-Duodu (Public Library of Science (PLoS), 2022)
Historically, infectious diseases have generated fears among populations. Unhealthy handling of these fears result in the stigma and discrimination of infected patients. Globally, measures taken so far by governments to curb the spread of the novel coronavirus disease-2019 (COVID-19) pandemic, although helpful, have created fears in people. Consequently, there are reported Ghanaian media cases of stigmatisation against persons who were infected and recovered from COVID-19. However, these reports remain unsubstantiated. This study, therefore, sought to examine stigma and discriminatory tendencies towards COVID-19 survivors among the adult population in Ghana. This was a population-based cross-sectional study among 3,259 adults. A multi-stage sampling technique was used to recruit study participants. Descriptive and inferential statistics comprising frequency, percentage, chi-square, and multivariable logistic regression were employed in analysing the data. Knowledge on COVID-19 was poor among 33.6% of the participants. Forty-three per cent had a good attitude towards COVID-19. Nearly half (45.9%) exhibited stigma and discriminatory tendencies towards COVID-19 survivors. Participants who had poor COVID-19 related knowledge (aOR = 1.91, 95%CI = 1.59-2.29, p<0.001) and poor attitude towards COVID-19 (aOR = 5.83, 95% CI = 4.85-6.98, p<0.001) were more likely to exhibit stigma and discriminatory tendencies towards COVID-19 survivors. Our study found relatively high proportions of poor knowledge and negative attitudes towards COVID-19. Stigma and discriminatory tendencies were consequently high. Our findings call for increased public education on COVID-19 by the Ghana Health Service and the Information Services Department, to increase the level of knowledge on the pandemic while reducing stigma and discrimination associated with it.